Interaction of Organic Cation with Water Molecule in Perovskite MAPbI3: From Dynamic Orientational Disorder to Hydrogen Bonding - Zhu, Zhuan; Hadjiev, Viktor G.; Rong, Yaoguang; Guo, Rui; Bo Cao; Tang, Zhongjia; Qin, Fan; Yang Li; Yanan Wang; Hao, Fang; Venkatesan, Swaminathan; Li, Wenzhi; et al. (Chemistry of Materials, 2016)
Microscopic understanding of interaction between H2O and MAPbI3 (CH3NH3PbI3) is essential to further improve efficiency and stability of perovskite solar cells. A complete picture of perovskite from initial physical uptake of water molecules to final chemical transition to its monohydrate MAPbI3·H2O is obtained with in situ infrared spectroscopy, mass monitoring, and X-ray diffraction. Despite strong affinity of MA to water, MAPbI3 absorbs almost no water from ambient air. Water molecules penetrate the perovskite lattice and share the space with MA up to one H2O per MA at high-humidity levels. However, the interaction between MA and H2O through hydrogen bonding is not established until the phase transition to monohydrate where H2O and MA are locked to each other. This lack of interaction in water-infiltrated perovskite is a result of dynamic orientational disorder imposed by tetragonal lattice symmetry. The apparent inertness of H2O along with high stability of perovskite in an ambient environment provides a solid foundation for its long-term application in solar cells and optoelectronic devices.